PRINCIPLES OF PERIODONTOLOGY: ETIOLOGY, PATHOGENESIS AND RISK MODIFIERS IN PERIODONTAL DISEASE. REVIEW - Maria-Alexandra Martu; Liliana Pasarin; Irina-Georgeta Sufaru; Ioana Martu; George-Alexandru Maftei; Stefana Nanu; Oana Bejan; Giorgio Nichitean; Odette Luca; Sorina-Mihaela Solomon (Romanian Dental Association for Education, 2021)
Periodontal diseases are arguably among the most ancient and common infectious diseases affecting humans, leading to permanent destruction of the supporting structures of the dentition and ultimately tooth loss. It has been established that dental biofilm (''plaque''), consisting of many microbial species and their products, is an etiological agent of periodontal disease. It is widely accepted that immunological and inflammatory responses to dental plaque via hostparasite interaction are manifested by clinical signs 40 Dentino et al. and symptoms of periodontal diseases.